ESG PRINCIPLES, SUSTAINABLE FINANCE, AND DIGITAL TRANSFORMATION IN THE MODERN FINANCIAL SECTOR - Nematillayeva Nargiza Shoxidaliyevna; Khusanov Salokhiddin (TADQIQOTLAR, 2026)
Abstract Environmental, Social, and Governance (ESG) principles have become one of the most influential frameworks in modern corporate governance, sustainable finance, and  investment  management.  ESG  standards  are  increasingly  used  to  evaluate corporate responsibility, ethical management, environmental sustainability, and long-term organizational performance. Financial institutions, governments, investors, and international organizations actively integrate ESG principles into strategic planning, investment analysis, and regulatory systems. The purpose of this article is to analyze the role of ESG in the financial sector, examine the relationship between ESG and digital transformation, and evaluate the opportunities and challenges associated with sustainable finance. The study explores the three pillars of ESG, the development of ESG  investing,  the  impact  of  artificial  intelligence  and  financial  technologies  on sustainability  management,  international  ESG  standards,  and  future  trends  shaping responsible  finance.  The  article  concludes  that  ESG  integration  significantly contributes to financial stability, transparency, innovation, and sustainable economic development.